Characterization and bioremediation potential of marine Psychrobacter species - Hanan M. Abd-Elnaby; Gehan M. Abou-Elela; Hanan A. Ghozlan; Halla Hussein; Soraya A. Sabry (Egyptian Journal of Aquatic Research, 2016)
Three marine Psychrobacter strains were isolated from seawater and sediments in Mediterranean Sea, Egypt, using culture-dependent techniques. Genotypic characterization for the three strains was performed using 16S rDNA sequence analysis. The Psychrobacter strains were screened for some physiological, biochemical characters, resistance to some antibiotics and heavy metals. All tested Psychrobacter strains were able to resist and accumulate several metals (Pb2+, Cu2+ and Cd2+) with variable degrees, depending on bacterial strains and metal ion species. Lead ions were easier to be bioaccumulated than the other two metals. Psychrobacter sp. H41A was the most potent strain in accumulation of the different metals. Psychrobacter sp. H41A accumulated 91.47 mg Pb2+/g fresh cells at optimum conditions of 60 min contact time, at 600 ppm and 30 °C. Plackett–Burman experimental design was applied to optimize the nutritional factors. The growth of Psychrobacter sp. H41A strain in the optimized culture medium increased the lead bioaccumulation 1.12-fold. The Psychrobacter strains were monitored for their ability to decolorize three different azo-dyes (fast orange, methanil yellow and acid fast red). Psychrobacter sp. H62 and H65 recorded the highest decolorization percentages (85% and 65%) with fast orange and methanil yellow, respectively.